The Philippine electronics code, volume 1: safety - Institute of Electronics and Communications Engineers of the Philippines ([Place of publication not identified] [Name of publisher not identified], 1977)
With the rapidly increasing use of electronic equipment for communication, medicine, research, in homes and in industry, standards ab=nd rules to help protect lives and properties from harmful effects resulting from its use become necessary .
Chapter I. General rules -- Chapter II. Definitions -- Chapter III. General electrical protection and grounding requirements -- Chapter IV. General strength requirements -- Chapter V. Indoor plant safety rules -- Chapter VI. Power sources -- Chapter VII. Outdoor plant safety rules -- Chapter VIII. Towers and support structures -- Chapter IX. Consumer products -- Chapter X. Test performance -- Chapter XI. Radiation Hazard .
Includes index.
Keywords: ELECTRONIC CODE; TECHNOLOGY